(untitled) (World Bulletin of Management and Law, 2023)
The current research aims to measure the effect of employee gratitude represented (feelings of gratitude, attitude towards gratitude, and behavior of gratitude) on strategic intelligence represented in (insight, vision, and motivation): the interactive role of tacit knowledge represented (using tacit knowledge, and the characteristics of implicit knowledge). A questionnaire was used to measure the level of availability of research variables at Asiacell Mobile Communications Company in Iraq of Al- Qadisiyah governorate which agents represent the policy of that company , and accordingly (70) questionnaire forms were distributed, and (67) valid for analysis were retrieved from them, and to reach the required results, the research adopted a set of statistical means that would ensure this, represented by the arithmetic mean, Standard deviation, correlation coefficient, and regression coefficient through the statistical package (SPSS V.26) and (AMOS V.26), and the research reached a set of results, the most important of which is the existence of a significant correlation and influence between employee gratitude, implicit knowledge, and strategic intelligence.